Structural Strength Analysis of Walker (Walking Aid Device) Using the Finite Element Method - AK faizin; N Hasan; LZ Faiza; NFR Supramono; P Bagas; GD Widagda; BY Saputro; MZ Purwananda (BIOMEJ, 2023)
One of the uses of a walking aid device (walker) is to support walking ability and balance effectively. The walker is a walking aid device that provides support for both weak legs and uses both hands for stability. This research aims to analyze the stainless steel as material in the design of the walker using finite element method through ANSYS. In the modelling process, the walker adopts the design from the website grabcad.com. In the simulation stage, the walker is subjected to a load of 1000N with fixed support conditions on all four legs, and then undergoes a meshing process with a size of 3 mm. The material applied to the walker model is stainless steel. Static structural analysis is performed in Ansys Workbench. The simulation results show a deformation value of 0.011272 mm, and the value of equivalent stress or von Mises stress should not exceed 207 MPa, while the stress occurring in the frame is 5.67 MPa. This is still considered safe as the simulation results are lower than the yield strength of the material, while the strain energy value is 0.00587 mJ.